2018
DOI: 10.1590/0100-3984.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of chemical-shift magnetic resonance imaging for the evaluation of osteoid osteoma

Abstract: ObjectiveThe purpose of this study was to determine whether chemical-shift magnetic resonance imaging (MRI) could be useful in the diagnosis of osteoid osteoma when clinical and radiological tumor features are inconclusive.Materials and MethodsThis retrospective study included 17 patients who underwent chemical-shift MRI for the evaluation of osteoid osteoma. For all patients, two musculoskeletal radiologists independently recorded signal intensities on in-phase and out-of-phase images in the nidus of the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…To the best of our knowledge, there are no other studies focusing on the use of CSI for the differentiation of RBMR and diffuse bone marrow involvement in hematological malignancies. However, there are studies investigating the contribution of CSI in the differentiation of benign-malignant fractures in the bones (10,14,18) and in the differential diagnosis of focal bone lesions (12,13,19,20). In these studies, SIR values of neoplastic compression fractures and focal malignant lesions were found to be significantly higher than the SIR values of benign fractures and lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are no other studies focusing on the use of CSI for the differentiation of RBMR and diffuse bone marrow involvement in hematological malignancies. However, there are studies investigating the contribution of CSI in the differentiation of benign-malignant fractures in the bones (10,14,18) and in the differential diagnosis of focal bone lesions (12,13,19,20). In these studies, SIR values of neoplastic compression fractures and focal malignant lesions were found to be significantly higher than the SIR values of benign fractures and lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Mean SI values of the vertebrae in out-of-phase and in-phase sequences were calculated. Signal intensity ratio (SIR) was calculated with the obtained values according to the "SIR = out-of-phase signal intensity value / in-phase signal intensity value" formula which was used in previous studies (12)(13)(14) to distinguish benign from malignant bone marrow involvement. The cut-off value for discriminating malignancies was calculated using ROC analysis.…”
Section: Mr Image Analysismentioning
confidence: 99%
“…However, the image of the tumor on the Xray is quite faint, the primary diagnostic imaging is on CT film with typical lesion which is the nidus in the center of the tumor, the surrounding is radiolucent area, the outside is the sclerotic bone (Figure 1) and on MRI is decreased signal image on T1 due to the bone marrow edema surrounding the tumor and increased signal on T2 (Figure 2). Some researchers have shown that MRI is a more sensitive image diagnosis method than CT though CT produces more specific images of osteoid osteoma (6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the musculoskeletal system by magnetic resonance imaging (MRI) has been the subject of a series of recent publications in the radiology literature of Brazil (4)(5)(6)(7)(8) . Although MRI is not considered the gold standard for the evaluation of hallux valgus, because MRI scans are not acquired during weight bearing, we agree with Helito et al (9) that MRI could be used for the diagnosis of this condition, given its high prevalence and the frequent unavailability of radiographic studies during weight bearing, as stated in their study published in the previous issue of Radiologia Brasileira.…”
mentioning
confidence: 99%